Determinants of information technology adoption among Malaysian farm-based enterprises - Adamkolo, M. I.; Hassan, Md. Salleh; Yusuf, S. (Universiti Putra Malaysia Press, 2016)
Information technologies (ITs) have been employed in various fields of human endeavour especially to engender socio-economic development. One key sub-sector in which the adoption of ITs is increasingly becoming critical in Malaysia is the farm-based (agri-based) enterprises. However, previous studies have suggested that a number of factors influences the adoption of ICT by enterprises, especially small and medium firms. This study was prompted by the need to determine the factors that influence the adoption of IT among farm-based enterprises. A pre-test study was conducted with 50 IT-using entrepreneurs selected from five farm-based firms that were selected using systematic random sampling from a population of 500 farm-based entrepreneurs (selected from 50 farm-based firms) in Selangor, Malaysia. The study applied modified Entrepreneurial Event Model (EEM) theory with System Support and Readiness and Perceived Benefits as independent variables, while IT Adoption was the dependent variable. The data was collected using a structured questionnaire and analysed using descriptive statistics and factor analyses. The findings revealed that System support and readiness and Perceived benefits are the critical factors that determine IT adoption and that most of the enterprises (M = 3.81, SD = 1.00) adopted basic entrepreneurial ITs while a number of them (M = 3.68, SD = 1.23) adopted advanced entrepreneurial ITs. The limitations of the study include the size of the sample. Recommendations for effective application of IT into practical usage for farm-based enterprises development were included.